Recent Progress in Diatom Research in the Yangtze River Basin - Hui Liu; Xiangqun Wu; Xu Chen (Limnological Review)
Diatoms have been widely used for aquatic environment assessment. However, the progress of diatom research is uneven in different regions of the world. This study gathered both Chinese and English articles on diatom research in the Yangtze River Basin in order to explore recent progress in this field. Using the Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang databases, we gathered 419 articles (1995–2024) on diatom research in the Yangtze River Basin. There is a substantial increase in the number of articles since 2000. Since the mid-1990s, a total of 63 new diatom species have been identified in this region. Based on limnological investigations of lakes in the Yangtze River Basin, diatom-based conductivity and total phosphorus (TP) transfer functions have been developed for quantitative reconstruction of past conductivity and TP in the water column. The results revealed a recent shift in thematic focus from eutrophication to biodiversity dynamics, the ecosystem regime shift, and ecohydrological change. Although diatom research in the Yangtze River Basin has achieved fruitful outputs, further studies are urgently needed to explore diatom biodiversity and the ecological status of aquatic ecosystems in this rapidly-developing region. The results can improve our understanding of diatom research progress and hence provide important clues for further studies.